Apps for librarians using the best mobile technology to educate, create, and engage - Hennig, Nicole (Libraries Unlimited, 2014)
"How can your library...and your patrons...benefit from mobile apps? This guidebook offers a solid foundation in "app-literacy," supplying librarians with the knowledge to review and recommend apps, offer workshops, and become the app expert for their communities"..